Reducing Salinity by Flooding an Extremely Alkaline and Saline Soil Changes the Bacterial Community but Its Effect on the Archaeal Community Is Limited - de León-Lorenzana, Arit S.; Delgado-Balbuena, Laura; Domínguez-Mendoza, Cristina; Navarro-Noya, Yendi E.; Luna-Guido, Marco; Dendooven, Luc (Frontiers in Microbiology, 2017)
Regular flooding of the soil to reduce salinity will change soil characteristics, but also the microbial community structure. Soil of the former lake Texcoco with electrolytic conductivity (EC) 157.4 dS m-1 and pH 10.3 was flooded monthly in the laboratory under controlled conditions for 10 months while soil characteristics were determined and the archaeal and bacterial community structure monitored by means of 454 pyrosequencing of the 16S rRNA gene. The EC of the soil dropped from 157.8 to 1.7 dS m-1 and the clay content decreased from 430 to 270 g kg-1 after ten floodings, but the pH (10.3) did not change significantly over time. Flooding the soil had a limited effect on the archaeal community structure and only the relative abundance of Haloferax-like 16S rRNA phylotypes changed significantly. Differences in archaeal population structure were more defined by the initial physicochemical properties of the soil sample than by a reduction in salinity. Flooding, however, had a stronger effect on bacterial community structure than on the archaeal community structure. A wide range of bacterial taxa was affected significantly by changes in the soil characteristics, i.e. four phyla, nine classes, 17 orders and 28 families. The most marked change occurred after only one flooding characterized by a sharp decrease in the relative abundance of bacterial groups belonging to the Gammaproteobacteria, e.g. Halomonadaceae (Oceanospirillales), Pseudomonadaceae and Xanthomonadaceae and an increase in that of the [Rhodothermales](Bacteroidetes), Nitriliruptorales (Actinobacteria) and unassigned Bacteria. It was found that flooding the soil sharply reduced the EC, but also the soil clay content. Flooding the soil had a limited effect on the archaeal community structure, but altered the bacterial community structure significantly.